Analisis Perbandingan Mazhab Syafi’i dan Hanbali Terhadap Hukum Wudlu dengan Air Musta’mal - Khoirus Sya'bani, Ahmad; Navilata, Fiki; Izzatul Ulya, Nayla; Siyono, Siyono (Jurnal ini dipublikasikan oleh Pusat Penelitian dan Pengabdian Publikasi (P3M) STAI Nahdlatul Watan Samawa-licensed under a Creative Commons Attribution-ShareAlike 4.0 International License., 2025)
This study examines the differences between the Shafi'i and Hanbali schools of thought regarding the law on the use of musta'mal water in wudu, which is an important issue in the practice of thaharah amid water scarcity and developments in water treatment technology. The purpose of this study is to analyze the differences and similarities in the arguments of the two schools of thought and their legal implications for the validity of wudu. This study uses a qualitative approach with a library research method, with data sources in the form of classical fiqh books and relevant scientific journal articles. Data analysis techniques were carried out through content analysis to examine the patterns of argumentation, the basis of istinbath law, and the methodology of determining the law of each school of thought. The results show that the Shafi'i school of thought views musta'mal water as pure but not purifying, so it is not valid for use in wudu, while the Hanbali school of thought argues that musta'mal water can still be used as long as it has not undergone any physical changes and has not been mixed with impurities. This difference reflects a difference in methodological approaches, whereby the Shafi'i school of thought emphasizes the principle of caution, while the Hanbali school of thought emphasizes the empirical condition of water. This study is expected to serve as a reference in the development of comparative fiqh studies and provide practical understanding for the community.